Drug-Induced Apnea in Children Admitted to Loghman Hakim Hospital, Tehran, Iran - GHOLAMI, Narges; ALWASABI, Fathi; FARNAGHI, Fariba (Iranian Journal of Child Neurology, 2017)
How to Cite This Article: Gholami N,Alwasabi F, Farnaghi F. Drug-Induced Apnea in Children Admitted to Loghman Hakim Hospital, Tehran, Iran. Iran J Child Neurol. Summer 2017; 11(3):15-18. Abstract Objective Environmental hazards, including poisons, can cause irreparable effects and even be fatal for children. Poisoning in children is common and serious, but often is preventable and treatable. This study aimed to evaluate the prevalence of drugs and chemical toxicity leading to apnea. In addition, we detected type of drug that induced apnea among children. Materials & Methods In a retrospective cross-sectional study from Apr 2012 to Apr 2013, sampled data of all hospitalized drug-induced apnea children were collected through hospital records. Results The most common cause of drug toxicity was methadone syrup (74%). The mortality rate was 3.1%; all of them due to methadone poisoning. Conclusion There was a high prevalence of apnea and poisoning of methadone in children. Methadone poisoning should be considered in apnea. References 1. Sheikh NA, Damodar G. Spectrum of Accidental Paediatric Poisoning at a Tertiary Care Centre in South India. Medico-Legal Update 2015;15(1):93-7. 2. Vasanthan M, James S, Shuba S, Abhinayaa J, Sivaprakasam E. Clinical profile and outcome of poisoning in children admitted to a tertiary referral center in South India. Indian J Child Health 2015;2(4):1-5. 3. Jepsen F, Ryan M. Poisoning in children. Current Paediatr 15(7):563-8. 4. Sharif MR, Nouri S. Clinical Signs and Symptoms and Laboratory Findings of Methadone Poisoning in Children. Iran J Pediatr 2015;25(1):e176. 5. Rudd RA, Aleshire N, Zibbell JE, Gladden RM. Increases in Drug and Opioid Overdose Deaths–United States, 2000-2014. MMWR Morbidity and Mortality Weekly Report 2016;64(50-51):1378-82. 6. Hein H, Puschel K, Schaper A, Iwersen-Bergmann S. [Accidental ingestion of methadone by children and suggestions for better prevention]. Archiv fur Kriminologie 2016;237(1-2):38-46. 7. Boutroy MJ. Drug-induced apnea. Biol Neonate 1994;65(3-4):252-7. 8. Farnaghi F, Hassanian-Moghaddam H, Faghihi Langroodi T. Fatal Poisoning and its Related Factors among Children Admitted in Loghman Hospital, 1995 -2004. Pajoohandeh J 2009;13(6):529-35. 9. Fariba Farnaghi, Narjes Jafari, Fatemeh-Fereshteh Mehregan. Methadone Poisoning among Children Referred to Loghman-Hakim Hospital in 2009. Pajoohandeh J 2012;16(6):299-303. 10. Saleem A, Ejaz MS, Arif F, Hanifa A, Habib MI. Factors leading to acute accidental poisoning in children. Quarterly Medical Channel 2015. 11. Farnaghi F, Pournasir Z, Tehranchi S. Opioid Poisoning in Children: A Report of 90 Cases. J Pediatr Nephrol 2015;3(2):62-6.